2019
DOI: 10.1139/apnm-2018-0788
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein concentrate limits venous thrombosis in rats

Abstract: To study the influence of whey protein concentrate (WPC-80) on the development of thrombosis, rats were supplemented with 2 doses of WPC-80 (0.3 or 0.5 g/kg) for 7, 14, or 21 days. Then, a 1-h venous thrombosis model was performed in half of the animals. Coagulation parameters, platelet count, and thrombus weight were assessed. Thrombus weight was decreased in rats obtaining WPC-80 and that was significant only for 14- and 21-day supplementation. There were slight differences between groups in coagulation para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…3 or 0. 5 g/kg) for 7, 14, or 21 days to see how it affected the development of thrombosis, and it was found that there were minor changes in andour findings are consistent with those (Tokajuk et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…3 or 0. 5 g/kg) for 7, 14, or 21 days to see how it affected the development of thrombosis, and it was found that there were minor changes in andour findings are consistent with those (Tokajuk et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…More precisely, Singh et al [ 28 ] found that whey protein and its components—lactalbumin and lactoferrin—improved energy balance and glycemic control against the onset of neurological deficits associated with stroke. Bioactive peptides from milk proteins were also responsible for the limitation of thrombosis [ 29 ] through their angiotensin convertase enzyme inhibitory potential, which might partly explain why the effect was found mainly for mortality from cerebral infarction in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies also indicated that α ‐lactalbumin could inhibit venous thrombosis. [ 47 ] and the coagulation was not initiated when the blood was exposed to materials with negatively charged surfaces such as misfolded proteins (unfolded BLA). [ 48 ] which was in accordance with our findings.…”
Section: Resultsmentioning
confidence: 99%